Response to COVID‐19 in Cyprus: Policy changes and epidemic trends. Issue 4 (3rd January 2021) - Kakoullis, Loukas; Eliades, Elias; Papachristodoulou, Eleni; Parperis, Konstantinos; Chra, Paraskevi; Constantinidou, Anastasia; Chatzittofis, Andreas; Sampsonas, Fotios; Panos, George
Abstract: Objectives: In late July, Cyprus experienced the second epidemic wave of COVID‐19. We present the steps taken by the government and evaluate their effect on epidemic trends. Materials: Cyprus Press and Information Office data were analysed. Using an R‐based forecasting program, two models were created to predict cases up to 01/09/2020: Model 1, which utilised data up to 09/06/2020, when airports reopened to foreign travelers with COVID‐19 screening; and Model 2, which utilised data until 24/06/2020, when screening for passengers from low‐transmission countries was discontinued. Results: PIO data revealed no significant policy changes between 24/06/2020 and 31/07/2020. Prediction models were robust and accurate (Model 1, R 2  = 0.999, P  < .001; Model 2, R 2  = 0.998, P  < .001). By August 30th, recorded cases exceeded those predicted by Model 1 by 24.47% and by Model 2 by 20.95%, with P values <.001 for both cases. Conclusions: The significant difference between recorded cases and those projected by Models 1 and 2 suggests that changes in epidemic trends may have been associated with policy changes after their respective dates. Discontinuation of major restrictions such as airport reopening, can destabilise the control of the epidemic, and may concomitantly necessitate a reevaluation of the current epidemic status. In the face of an evolving situation such as the COVID‐19 pandemic, states are forced to balance the imposing of restrictions against their impact on the economy.